City Clubs : critical success factors and prototype design. - Loo, Daisy. (2009)
Presently, city clubs are categorised by member's club and proprietary club. Few investors think of putting his money in developing city clubs when he intended to invest in the hospitality industry. The authors disclosed that by re-categorising the city clubs, distinct categories which serve four different needs viz. recreation, family, networking and exclusivity needs can be found in city clubs that otherwise looked the same superficially. The authors focused their study on five city clubs in Singapore each of which is the representative of one of the four categories. Characteristics of the five city clubs studied include image and positioning, objective and commitment, current and past strategies, organisation and culture, cost structure, strengths and weaknesses, size, growth and profitability. Critical success factors of these clubs were identified subsequently. This approach is an attempt to enable investors to examine city clubs in depth.